RESILIENSI DAN FEAR OF MISSING OUT DI PT X PALANGKA RAYA - Pazya Ivana Novriasi; Sutarto Wijono (Bajang Institute, 2026)
This study seeks to explore the relationship between resilience and Fear of Missing Out (FoMO) among employees at PT X Palangka Raya. FoMO has become increasingly significant in today’s workplace, where individuals are expected to remain continuously connected to information and social interactions. A quantitative correlational method was applied, involving 153 employees selected through purposive sampling. Data were gathered using resilience and FoMO measurement scales that have demonstrated adequate validity and reliability. The findings from the Spearman correlation analysis revealed a significant positive association between resilience and FoMO, although the strength of the relationship was relatively weak. These results suggest that resilience does not necessarily reduce FoMO; instead, in certain contexts, it may be linked to higher levels of social engagement. Consequently, effective management strategies are required to minimize the potential negative effects of FoMO on employee well-being and productivity. Overall, these results emphasize the need to better understand the nuanced role of resilience in workplace settings, particularly in addressing FoMO to enhance both employee well-being and organizational performance.